Chapter 3 Conceptualizing re-domestication theoretical reflections and empirical findings to a neglected concept - Peil, Corinna (Taylor & Francis, 2023)
Chapter 3: This chapter takes an in-depth look at the notion of re-domestication and fills a theoretical gap by proposing a sound and empirically supported conceptualization. Although some domestication studies refer to re-domestication as a turning point in the domestication process, a consistent and unified understanding of this term is lacking. To address this, historical and current domestication studies that address re-domestication are first critically reviewed and discussed. Subsequently, a conceptualization of re-domestication is proposed based on theoretical and empirical research. Accordingly, re-domestication is conceived as the re-inscription of a medium into everyday domestic life, which is linked to a transformation of established domestic communication cultures. In a total of three case studies on the re-domestication of the Internet and television, it is then shown in more detail which dynamics related to everyday life must be at play in order to be able to speak of a re-domestication process.